Personality Determinants Related to the Use of Selective and Effective Dietary Supplements by Elite Polish Team Sport Athletes - Maria Gacek; Agnieszka Wojtowicz; Adam Popek (MDPI AG, 2024)
Introduction: The purpose of this research was to analyse relationships between personality traits and the use of selected dietary supplements among Polish athletes training in team sports. This subject matter has not been explored in prior research. Material and Methods: This research was carried out among a group of 213 athletes (men) in the 18-36 age range, with the implementation of a proprietary validated questionnaire for the use of dietary supplements and the NEO-PI-R inventory (Neuroticism-Extraversion-Openness Personality Inventory-Revised). Statistical analyses were performed with the Kruskal-Wallis and Mann-Whitney tests, assuming the following level of significance: α = 0.05. Results: It was shown that athletes who periodically and regularly consumed isotonic drinks, as well as energy bars and gels, were characterised by a lower level of neuroticism than those who did not consume them. Athletes who periodically took multivitamin preparations were characterised by a lower level of extraversion and openness, and those periodically using multimineral preparations were characterised by a higher level of agreeableness than those who did not use these agents. Athletes not taking creatine were characterised by the lowest level of conscientiousness among the study participants. The use of protein nutrients, probiotics and caffeine was not associated with any personality traits in the athletes. Conclusions: Further relationships of the Big Five personality traits were demonstrated with the use of effective dietary supplements by athletes; the most unambiguous correlations were described for neuroticism and conscientiousness in such a way that the use of isotonic drinks, as well as energy bars and gels, was connected with a low level of neuroticism, while the use of creatine was connected with high conscientiousness.